The Influence of the Amplitude Spectrum Correction in the HFCC Parametrization on the Quality of Speech Signal Frame Classification - GMYREK, Stanislaw; HOSSA, Robert; MAKOWSKI, Ryszard (Archives of Acoustics, 2025)
The voiced parts of the speech signal are shaped by glottal pulse excitation, the vocal tract, and the speaker’s lips. Semantic information contained in speech is shaped mainly by the vocal tract. Unfortunately, the quasiperiodicity of the glottal excitation, in the case of HFCC parameterization, is one of the factors affecting the significant scatter of the feature vector values by introducing ripples into the amplitude spectrum. This paper proposes a method to reduce the effect of quasiperiodicity of the excitation on the feature vector. For this purpose, blind deconvolution was used to determine the vocal tract transfer function estimator and the corrective function of the amplitude spectrum. Then, on the basis of the obtained HFCC parameters, statistical models of individual Polish speech phonemes were developed in the form of mixtures of Gaussian distributions, and the influence of the correction on the quality of classification of speech frames containing Polish vowels was investigated. The aim of the correction was to narrow the GMM distributions, which, according to detection theory, reduces the classification errors. The results obtained confirm the effectiveness of the proposed method.